The flicker - Edgmon, H. E. (Feiwel & Friends, 2024)
With their parents dead and supplies running low after a solar flare scorched the Earth, stepsisters Millie and Rose leave home with their infant half brother and dog Corncob in search of Millie's grandma, a Seminole elder.